When a Tsunami Strikes: A Mobility Model for Coastline Cities - Rosas-Olivos, E (Institute of Electrical and Electronics Engineers Inc., 2018)
Every year, hundreds of natural phenomena hit the world, unleashing major disasters and compromising the welfare of millions of people and public infrastructure. On a planet made up of over 70% water, tsunamis are a latent risk that threatens civilians all over the world. Hopefully, technological advances have provided the development of monitoring systems that enable predicting this kind of phenomena and evacuating high risk flooding zones. Nowadays, mobile communication in a post disaster scenario is critical to support all the post disaster tasks. However, developing useful algorithms and applications to support problems arising on these scenarios require large scale real-life testing, which are generally out of the reach of scientists and application developers. In this context, simulation provides an effective tool to assess the performance of software solutions in close-to-real disaster scenarios. In this work, we propose a new mobility model for tsunami scenarios that includes information published by the Chilean National Office for Emergency (ONEMI) about evacuation routes and security points. We have tested and compared our proposal using the One simulator. © 2017 IEEE.